I'd die for you : and other lost stories - Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Scribner, 2017)
"Known not only for his brilliant novels bur also for short stories chronicling the Jazz Age, such as "Bernice bobs her hair" and "The diamond as big as the Ritz", F. Scott Fitzgerald continued to write stories his entire life, some of which were never published- until now. Many of the stories in I'd Die for You were submitted to major magazines and accepted for publication during Fitzgerald's lifetime but were never printed. A few were written as movie scenarios and sent to studios or producers, but not filmed. Others are stories that could not be sold because thier subject matter or style departed from what editors expected of Fitzgerald in the 1930s. They come from various sources, from library archive to private collections, including those of Fitzgerald's family."-- book flap